(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Contemporary ethics faces significant challenges due to the increasing intersection of science and morality, particularly regarding planetary responsibility and intergenerational justice. The ecological crisis must not be viewed merely as a byproduct of human actions, but as an urgent issue demanding a profound transformation in global behaviors. While technological progress has led to advancements, it has also introduced new risks, highlighting the need for a reexamination of ethical foundations. Hans Jonas’ proposal, with his ethics of responsibility, offers an essential philosophical framework, advocating for the responsibility of current generations for the long-term consequences of their actions on the environment and future generations. The concept of intergenerational justice, understood as justice between generations, discussed in the works of Hans Jonas and John Rawls, is intrinsically linked to the common good and is one of the central principles of Pope Francis’ Laudato Si’ encyclical. The encyclical aims to balance technological progress with the ethical responsibility of protecting humanity and all living beings on planet Earth. Pope Francis emphasizes that the real challenge lies not in rejecting progress, but in mitigating the risks that threaten human dignity and planetary sustainability. This article proposes a dialogue between Jonas’ thought and Pope Francis’ reflections, exploring how the ethics of responsibility can be applied to the contemporary ecological context. Furthermore, drawing from Jonas’ contributions, the article examines the relevance of Romano Guardini and Edith Brown Weiss’s theories in the development of intergenerational ethics, analyzing how their ideas on power and equity deepen the understanding of justice between generations. Thus, the study aims not only to provide a theoretical foundation for the ethics of responsibility and intergenerational justice, but also to highlight the urgency of reflections that offer both theoretical and practical solutions to address the ecological crisis, ensuring the sustainability and survival of humanity and the planet.